matjay1307
matjay1307
01-10-2019
Mathematics
contestada
Solve for b: 2(b + 3) = b – 4
Respuesta :
willjohnsonnguyen
willjohnsonnguyen
01-10-2019
Answer:
b = -10
Step-by-step explanation:
2(b + 3) = b – 4
2b + 6 = b - 4
-b -b
b + 6 = -4
-6 -6
b = -10
Answer Link
kaymccracken
kaymccracken
01-10-2019
The answer is; B = (-10)
Answer Link
VER TODAS LAS RESPUESTAS ( 32+ )
Otras preguntas
what early river civilization does the chart describe?
What is the major difference between a persuasive essay and an argumentative essay? An argumentative essay does not try to change a reader's opinion. An argum
for his long distance phone service, manuel pays a $2 monthly fee plus 12 cents per minute. last month, manuel's long distance bill was $14.36 . for how many mi
you would like to join a fitness center. fit-n-trim charges $80 per month. fit-for-life charges a one time membership fee of $75 and $55 per month. which fitnes
what percentage of terrorist incidents involve explosives
smith, a candidate running against the current senator, says, "the senator has voted against health care. she is not in line with the principles of our party."
Z varies inversely with the product of x and y. When x=2 and y=4, z=0.5 what is the value of z when x=4 and y=9?
3x + 2y = 4 2x - y = 5 (a) This system of equations has no solution. (b) has one solution. (c) is coincident.
Which phrase best defines a gene
what is a benefit of using nonrenewable resources?